2008
DOI: 10.1152/ajpcell.00228.2007
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrases IV and IX: subcellular localization and functional role in mouse skeletal muscle

Abstract: The subcellular localization of carbonic anhydrase (CA) IV and CA IX in mouse skeletal muscle fibers has been studied immunohistochemically by confocal laser scanning microscopy. CA IV has been found to be located on the plasma membrane as well as on the sarcoplasmic reticulum (SR) membrane. CA IX is not localized in the plasma membrane but in the region of the t-tubular (TT)/terminal SR membrane. CA IV contributes 20% and CA IX 60% to the total CA activity of SR membrane vesicles isolated from mouse skeletal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 46 publications
6
23
0
1
Order By: Relevance
“…Rather, using antisera to human CAIV, a specific immunostaining, fully coincident with the histochemical staining, was found in the villus cavity cells of the chick chorioallantoic membrane 20 . Although a conclusive characterization of such a membrane-associated CA remains to be achieved, its functional meaning might be consistent with that attributed to mammalian CAIV at the different sites where it proved to be expressed [22][23][24][25] . In the quail lingual glands, a putative membrane-associated CA isoform at the basolateral borders of the secretory cells might serve, analogously to CAIV isoenzyme, to regulate the extracellular pH and, thereby, contribute to maintaining the balance of the oral environment.…”
Section: Discussionmentioning
confidence: 56%
“…Rather, using antisera to human CAIV, a specific immunostaining, fully coincident with the histochemical staining, was found in the villus cavity cells of the chick chorioallantoic membrane 20 . Although a conclusive characterization of such a membrane-associated CA remains to be achieved, its functional meaning might be consistent with that attributed to mammalian CAIV at the different sites where it proved to be expressed [22][23][24][25] . In the quail lingual glands, a putative membrane-associated CA isoform at the basolateral borders of the secretory cells might serve, analogously to CAIV isoenzyme, to regulate the extracellular pH and, thereby, contribute to maintaining the balance of the oral environment.…”
Section: Discussionmentioning
confidence: 56%
“…However, we did not ensure it due to unknown reasons. CA9 is known to express in the fetal musculoskeletal system to maintain pH against hypoxia (Schultz et al, 2011;Liao et al, 2009;Scheibe et al, 2008). Strong CA9 expression in the cartilaginous pulley and the tendon of the superior obliquus muscle seemed to correspond to a fact that the adjacent fetal joint surfaces are positive for CA9 (Schultz et al, 2011) and suggested a mechanical stress between the developing pulley and tendon.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in contrast to other CAs isoenzymes, CA9 expression was reported in fetal joint cartilages, tendons and ligaments those receive mechanical stress due to increased size of the adjacent structures (Schultz et al, 2011;Liao et al, 2009;Scheibe et al, 2008). Therefore, we attempted to clarify spatial expression of CAs, especially CA9, in human fetus extra-occular tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Flotillin 2 is not expressed in skeletal muscle cells [32]; however, there may still be an unknown partner for flotillin 1 to form flask structures. It is notable that the glycophosphatidylinositol-anchored carbonic anhydrase IV was recently localized to transverse tubule openings in mouse skeletal myofibers [33], and it is possible that this protein and flotillin 1 reside in the same lipid rafts.…”
Section: Discussionmentioning
confidence: 99%